Pharmacological activities and molecular mechanisms of pure and crude extract of Andrographis paniculata: An update - Sharuti Mehta, M. Pharmacy; Anil Kumar Sharma, Ph.D.; Rajesh K. Singh, Ph.D. (Phytomedicine Plus, 2021)
Background: Andrographis paniculata (Burm.f.) Nees (Acanthaceae) is a herbaceous plant used in traditional medicines for the treatment of various ailments. Diterpene lactones are the main phytoconstituents and are responsible for the plant's bitter taste and therapeutic activity. Pure andrographolide (AD) and crude extracts have all been shown to be accountable for various pharmacological activities, including anticancer, anti-inflammatory, hepatoprotective, immunomodulatory, neuroprotective, antidiabetic and antibacterial agents. This review covers recent studies of the exploitation of A. Paniculata with a specific focus on the plant's pharmacological and clinical studies alongwith their therapeutic drug targets and novel drug delivery system. Method: Information for the current review article is collected from various electronic scientific databases such as Science Direct, PubMed, Scopus, Scifinder, Google Scholar, books and reports. All the composed information is classified into different sections according to the objective of the paper. To fetch the useful articles various keywords, namely 'Andrographis paniculata’, ‘King of Bitters’, ‘Andrographolide’ ‘Clinical study’, Molecular mechanism’, ‘Anticancer’, 'Anti-inflammatory', 'Antidiabetic', 'Neuroprotective', ‘Pharmacokinetics’, ‘Novel Drug Delivery System’ were used for search. Results: Of all the 180 studies, twenty one primarily focused on introduction, twenty-seven studies presented a brief introduction of different diseases, ninety studies highlighted the pharmacological activities and therapeutic targets of plant extract and its pure bioactive compounds, twenty five investigations demonstrated the pharmacokinetic parameters of AD and its novel drug delivery systems and seventeen studies investigated clinical studies of the plant. Conclusion: Different recent research and review papers have been studied to gain insights into the therapeutic activities and clinical studies of A. paniculata. Following the extensive literature survey, we collected notable information on the plant. For rapid glance studies, experimental and research findings are compiled into tabular form for quick understanding. Possible directions for future research are also outlined briefly, encouraging the researchers for advance investigations on various mechanistic targets of this plant.